Interpersonal communication - Knapp, Mark L.; Daly, John A. (John Augustine), 1952-; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2010)
Interpersonal communication is inexorable, irrevocable, complex & relative but ultimately necessary. Understanding this type of communication gives us a framework for successful & effective interaction with others in everyday situations. In this four volume set, the authors explore the dynamics & implications of interpersonal communication.
v. 1. Introduction, history and communicator characteristics -- v. 2. Processes and messages -- v. 3. Forming and maintaining relationships -- v. 4. Persuasion and competence.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Interpersonal communication; Electronic books